Development and implementation of a high-fidelity simulation training course for medical and nursing collaboration based on the Fink integrated course design model - Jiang, Meng-Han; Dou, Li-Wen; Dong, Bo; Zhang, Man; Li, Yue-Ping; Lin, Cui-Xia (Frontiers in Medicine, 2024)
The purpose of this study is to examine the design and implementation of a high-fidelity simulation training course for medical and nursing collaboration, based on the Fink integrated course design model. Additionally, the study aims to validate the teaching effectiveness of the course.Previous empirical studies have highlighted the effectiveness of collaborative healthcare education in institutional teaching and hospital training. However, the development of healthcare collaborative education in China has been slow to develop in China. In recent years, Chinese nursing educators and researchers have shown interest in utilizing high-fidelity simulators for healthcare collaborative education. These simulators help address the limitations of traditional nursing teaching and healthcare separation simulation. Nevertheless, a standardized simulation interprofessional education curriculum is still lacking. Therefore, nursing educators need to develop a standardized high-fidelity simulation training curriculum for healthcare collaboration, guided by 2 established science curriculum development theories. Methods A high-fidelity simulation training course on healthcare collaboration was designed based on the Fink integrated curriculum design model. The course was taught to 14 nursing students and 8 clinical medicine students from March to July 2022. To comprehensively evaluate the effectiveness of the healthcare collaboration high-fidelity simulation training course, several assessment tools were used. These included course grades, satisfaction and self-confidence scales, simulation teaching practice scales, healthcare collaboration attitude scales, critical thinking skills scales, and semi-structured interviews.After the course was implemented, students demonstrated high overall scores (79.19±5.12) and reported high satisfaction ratings (4.44±0.37). They also exhibited increased self-confidence (4.16±0.33). Additionally, students evaluated all four dimensions of the course teaching practice scale positively. Furthermore, the study demonstrated significant improvements in various aspects, such as attitudes towards medical and nursing collaboration (t=-7.135, P<0.01), shared education and teamwork (t=-3.247, P=0.002), job autonomy for nurses (t=-1.782, P=0.000), and reduced physician dominance (t=-6.768, P=0.000). The critical thinking skills of the students showed significant improvement, with higher scores in truth-seeking (t=-3.052, P=0.004), analytical ability (t=-2.561, P=0.014), systematic ability (t=-3.491, P=0.001), self-confidence in critical thinking (t=-4.024, P=0.000), and curiosity (t=-5.318, P=0.000) compared to their scores before the course (all P<0.05). The interviews showed that the course's student-centered approach enabled active learning.